Improving Company Performance using Financial Planning Approach Toward Fragrance Companies: A Case Study of Saja - Salmatun Nafisah; Irawan, Atika (Integrasi Sains Media, 2024)
The perfume industry has experienced significant shifts towards using natural oils and synthetic components, driven by changing customer preferences and increased awareness of natural products. Saja, a perfume company established in 2022, aims to capitalize on this growing trend by offering natural products. Despite its potential, the company faces financial challenges due to a lack of strategic financial planning. An analysis of Saja's financial performance from late 2023 to mid-2024 revealed inconsistent income and fluctuating cash flow, as identified through financial ratios and DuPont analysis. These issues highlight the company's low financial performance. To address these challenges, Saja plans to enhance its financial planning by optimizing budget allocations, increasing production cost efficiency, and expanding product and market segments to boost income and reduce expenses. The sustainability of this strategy was assessed using three economic and risk scenarios: realistic, optimistic, and pessimistic. The feasibility of the proposed strategy was measured through the Payback Period (PP) in future and present value, Internal Rate of Return (IRR), and Net Present Value (NPV). Results indicate that the proposed financial strategy is acceptable and feasible, suggesting that its implementation would improve Saja's financial performance.